POETICS OF NARRATIVE STRUCTURES IN THE TEXTS OF VASYL STEFANYK - Nakonechna, Larysa; Nakonechna, Liudmyla (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article is devoted to the topic of poetics in Vasyl Stefanyk's short stories. The purpose of the article is to analyze the poetics of narrative structures of Vasyl Stefanyk's works on the example of motive-thematic complex of death, to consider also features of descriptive structures of the writer, in particular combination and interaction of descriptive and narrative manners. This goal was possible to be achieved by using the research methods, namely: analysis and synthesis, comparison, specification, and generalization. The authors explore the issues of poetics of narrative structures on the basis of the texts of short stories "Maple Leaves", "Funeral", "Lan", "May" and others. Comparisons of descriptive and narrative elements in Vasyl Stefanyk's short stories are made mainly on the basis of a thorough study of the problems of Gerard Genet's poetics "Figures". The authors focused on the analysis of narrative structures, the peculiarities of the combination and interaction of descriptive and narrative manners of the writer, the functions of the strategy of visualization and descriptiveness in the narrative texts of Vasyl Stefanyk. This is the practical value and novelty of the presented study. The authors found that the principle of visualization allows adding a moment of descriptiveness to the narrative text. Considering the distinction and interaction of visualization and descriptiveness in the texts of Vasyl Stefanyk, the authors trace the moments of transition (or intersection/overlap) of passages in a descriptive and narrative manner of narrative. In addition, the authors of the article analyzed the relationship of time and space dimensions in texts to narrative and descriptive structures. Analysis of Vasyl Stefanyk's short stories through the prism of the interaction of ekphrasis and diegesis opens up completely new perspectives on the interpretation of the text. The high frequency of descriptive structures in Vasyl Stefanyk's texts may be one of the signs of genre heterogeneity in the writer's works.